Retrenchment : the law and practice in Malaysia - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (Thomson Reuters Malaysia Sdn Bhd, 2012)
The employer is empowered to devise measures to reorganise and restructure or manage their workforce in any manner they deem appropriate to improve its profitability. Retrenchment of workers based on operational requirements is recognised for example, when there is reduction, diminution or cessation of the type of work the employee is performing. The excess services of employees resulting from a genuine reorganisation scheme adopted for reasons of economy and better management of the business may be discharged. Thus, a genuine redundancy in the organisation must be established before the retrenchment of surplus labour could be justified. However, the decision to retrench workers must not be capricious, without reason, mala fide, actuated by victimisation or unfair labour practice.